Characterization of a low-cost PIN photodiode for dosimetry in diagnostic radiology. Issue 1 (February 2015) - Romei, Chiara; Di Fulvio, Angela; Traino, Claudio Antonio; Ciolini, Riccardo; d'Errico, Francesco
Abstract A commercial silicon PIN-photodiode was tested and characterized as ionizing radiation detector for radiological applications. A current-to-voltage amplification stage was designed and realized in order to acquire the photodiode signal in current mode. The system was tested with clinical beams routinely used for radiography and mammography. A Monte Carlo simulation of the detector was performed with the MCNPX code in order to model and fully understand, in particular, the impact of the sensor casing on the low energy response of the device. A reproducible output linearity was found over the dose range 0.03–4.5 mGy of great clinical relevance. The system sensitivity was found to be stable at 0.2 V s Gy−1 for effective X-ray energies between 17 and 40 keV. The batch-to-batch reproducibility of the diodes was also experimentally investigated for two different batches of 14 diodes each. An inter-comparison with dosimeters routinely used in medical physics (i.e. Barracuda MPD RTI) showed a linear correlation between PIN-photodiode readout and absorbed dose measured with Barracuda, in the range of doses received by mammography and radiology patients.